2015
DOI: 10.3758/s13415-015-0356-5
|View full text |Cite
|
Sign up to set email alerts
|

Individual difference in prepulse inhibition does not predict spatial learning and memory performance in C57BL/6 mice

Abstract: The startle reflex to an intense acoustic pulse stimulus is attenuated if the pulse stimulus is shortly preceded by a weak non-startling prepulse stimulus. This attenuation of the startle reflex represents a form of pre-attentional sensory gating known as prepulse inhibition (PPI). Although PPI does not require learning, its expression is regulated by higher cognitive processes. PPI deficits have been detected in several psychiatric conditions including schizophrenia where they coexist with cognitive deficits.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
1
5
0
1
Order By: Relevance
“…OFT are two commonly used detection methods. 30 The present study showed that the experimental rats exposed to PM 2.5 displayed significantly decreased space cognitive and exploratory behavior abilities in the new environment. PM 2.5 exposure may lead to a decline in the function of learning and memory in rats.…”
Section: Discussionsupporting
confidence: 50%
“…OFT are two commonly used detection methods. 30 The present study showed that the experimental rats exposed to PM 2.5 displayed significantly decreased space cognitive and exploratory behavior abilities in the new environment. PM 2.5 exposure may lead to a decline in the function of learning and memory in rats.…”
Section: Discussionsupporting
confidence: 50%
“…Recently, cognitive traits of inbred animal models have been used to understand “personality” at the biological level [ 4 ]. For instance, a specific link has been revealed between working memory and sensorimotor gating in inbred C57BL/6NCrl mice [ 5 ], which has not been reproduced in another study [ 6 ]. These rodent studies demonstrate that some behavioral traits are significantly associated in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…We noticed that participants needed to remember different numbers of features in different visual search conditions, resulting in differences in WM load between the conditions. A significant correlation between PPI and WM has been reported, showing that higher PPI can predict better performance on WM tasks (Peleg-Raibstein et al, 2015;Singer et al, 2013). However, this association has not been consistently observed across all PPI tests (Csomor et al, 2008).…”
Section: Methodsmentioning
confidence: 99%